Pengaruh Penyelesaian Sengketa Tanah Terhadap Pengadaan Tanah Dalam Kegiatan Pembangunan Bendungan Paselloreng Kecamatan Gilireng Kabupaten Wajo - Syamsiar Syamsiar; Zulfachri Zulfachri; Nur Avni Dhuha (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Land disputes hampered the process of providing compensation for land acquisition and created legal uncertainty over land ownership for the construction of the Paselloreng Dam, Gilireng District, Wajo Regency. This study aims to determine how good the effect of land dispute settlement on land acquisition in the construction of the Paselloreng Dam, Gilireng District, Wajo Regency. The type of research used is census research using a quantitative associative approach with descriptive study methods. Data collection techniques used are questionnaires/questions, documentation and observation. The population of this study is the people who are in dispute and a sample is drawn. The results of this study indicate that land disputes are in a fairly good category and there is a positive influence between land disputes on land acquisition for the construction of the Paselloreng Dam, Gilireng District, Wajo Regency.